Institutional Capacity Development (Capacity Building) Of Village-Owned Business Enterprises in Tambayoli Village, Soyo Jaya Sub District, North Morowali District, Indonesia - Abdul Rivai; Nasrullah Nasrullah; Hasanuddin Hasanuddin; Vernanda Chrisstin; Fitrina Fitrina; Dandan Haryono (Qubahan Academic Journal)
The aim of this research is to find out why the development of institutional capacity of village-owned enterprises in Tambayoli Village, Soyo Jaya District, North Morowali Regency, Indonesia, has not been effective. This research uses qualitative research methods. We collected data through in-depth interviews with administrators of village-owned enterprises, community leaders and village officials. We conducted participatory observation to gain direct understanding of the management dynamics of village-owned enterprises. In addition, we used documentation studies to collect secondary data from annual reports of village-owned enterprises, village regulations, and other related documents. We carried out data analysis using a three-step technique, which includes data collection, data condensation, drawing conclusions, and verification. Research findings show that developing the institutional capacity of Village-Owned Enterprises in Tambayoli Village, Soyo Jaya District, North Morowali Regency, Northern Indonesia, has not been effective. This is caused by the first factors from the individual dimension such as the lack of a training budget organized by the government, the absence of incentives or honorarium for administrators, and there have never been any training activities, secondly the organizational dimension, the lack of a clear vision and mission, mature plans, management adequate, as well as clear and definite efforts have hampered the development of the institutional capacity of village-owned enterprises. thirdly, the ineffectiveness of this system stems from the lack of detailed understanding and proper application of regulations by all Tambayoli Village stakeholders. The research results show that the village body of Tambayoli Village has not effectively developed its institutional capacity.